Role of Family System, Positive Emotions and Resilience in Social Adjustment among Pakistani Adolescents - Najam-us Sahar; Naila Muzaffar Muzaffar (Universitas Ahmad Dahlan, 2017)
AbstractThe present study explored the role of positive emotions, resilience & family system in social adjustment in Pakistani adolescents. Through convenient sampling, data collected from 150 adolescents (70 boys & 80 girls).In terms of family system 92 were living in nuclear family while 58 injoint family. Urdu version of Modified Differential Emotions Scale, Resilience Scale and Bell`s Adjustment Inventory were used. Statistical analysis revealed the presence of significant positive relationship between positive emotions and resilience (r = .39**) where girls were slightly more resilient (M ± SD = 120.77 ± 24.03) & socially adjusted (M ± SD = 17.41 ± 4.15). Moreover 52 % adolescents reported difficulty in talking with new people. Majority of participants from Joint family reported good social adjustment (38%) and high resilience (17%) as compared to those in nuclear family (21%, 13%). The influence of these demographic variables is important indication to be explored further.Keyword: Family system, Positive emotion, and resilience